Varieties of lunar meteorites recovered from Antarctica - Yanai, Keizo; Kojima, Hideyasu (National Institute of Polar Research, 1991)
P(論文) By the 1988-1989 field season, more than 10 specimens of lunar meteorites have been recovered in Antarctica by the U. S. and Japanese Expeditions. The specimens from the Yamato Mountains, Allan Hills and MacAlpine Hills (Y-791197,Y-82192/193,Y-86032 [1], ALHA81005 [2], MAC88104/105) are all plagioclase (anorthite)-rich breccias from the lunar highlands. Y-793274 is a pyroxene-and plagioclase-rich breccia, and EET87521 [5] is basaltic clast-rich breccia : Both contain abundant components from the basaltic provinces (the maria) of the lunar crust. Asuka-31 and Y-793169 are unbrecciated, coarsegrained rocks consisting mainly of pyroxene and plagioclase (maskelynitized), together with ilmenite and troilite. The bulk compositions of Asuka-31 and Y-793169 are very similar to low-titanium and very low-titanium (VLT) lunar mare basalts. Oxygen isotope data strongly support the lunar origin of all the Antarctic lunar meteorites. The FeO/MnO ratios are consistent with the range of those of lunar pyroxenes, which are markedly different from those of basaltic achondrites. However, they contain a wide range of pyroxene compositions. The lunar meteorites have originated from several different places on the Moon surface, comprising single rock facies or monomict-polymict breccia facies. On the basis of lithology, texture, petrography, chemistry and mineral compositions, the lunar meteorites can be divided into 4 or more different types : namely anorthositic breccias (including 3-4 different facies), basaltic-anorthositic breccias, basaltic breccias, and unbrecciated diabase and gabbro. These types indicate that the samples might have originate from at least 7 different sites on the near-and far-side sites of the Moon. The different types of lunar meteorites strongly suggest that there are other unknown rock type (s) on the Moon, and that new meteorite types are to be expected in Antarctica. departmental bulletin paper